Silver nanoparticle embedded copper oxide as an efficient core–shell for the catalytic reduction of 4-nitrophenol and antibacterial activity improvement. Issue 27 (27th June 2018) - Bouazizi, N.; Vieillard, J.; Thebault, P.; Desriac, F.; Clamens, T.; Bargougui, R.; Couvrat, N.; Thoumire, O.; Brun, N.; Ladam, G.; Morin, S.; Mofaddel, N.; et al.
Abstract : A facile and eco-friendly method was developed to prepare a microporous CuO@Ag 0 core–shell with high catalytic and antibacterial activities. Abstract : A facile and eco-friendly method was developed to prepare a microporous CuO@Ag 0 core–shell with high catalytic and antibacterial activities. Scanning and transmission electron microscopy revealed a preponderance of nearly spherical 50 nm particles with slight structure compaction. Comparison of the hysteresis loops confirmed the structure compaction after AgNP incorporation, and a significant decrease of the specific surface area from 55.31 m 2 g −1 for CuO to 8.03 m 2 g −1 for CuO@Ag 0 was noticed. A kinetic study of 4-nitrophenol (4-NP) reduction into 4-aminophenol (4-AP) with sodium borohydride revealed a first order reaction that produces total conversion in less than 18 minutes. CuO@Ag 0 also exhibited appreciable antibacterial activity against Staphylococcus aureus . The antibacterial effects were found to strongly depend on the size, contact surface, morphology and chemical composition of the catalyst particles. The addition of Ag 0 -NPs produced more reactive oxygen species in the bacteria medium. These results open promising prospects for its potential applications as a low cost catalyst in wastewater treatment and antibacterial agent in cosmetics.